2017
DOI: 10.1037/lat0000064
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment among young Puerto Rican mothers: Perceived partner support and the moderating role of Latino cultural orientation.

Abstract: Adolescent mothers face multiple stressors and are at risk for experiencing high levels of depressive symptoms and parenting stress. This study examined the interplay of Latino cultural orientation and perceived support from romantic partners in protecting the adjustment of young, low-income, Puerto Rican mothers (N = 103; M age = 18.0 yrs; SD = 1.2) during the second year postpartum. In multivariate analyses, perceived partner support was uniquely and negatively associated with both maternal depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…Additionally, our findings extend the literature indicating the negative impact that partner strain can have on emotional states in this population. Given the effort often dedicated to maintaining partner relationships, the diminished self-worth and devalued identity following the failure of a romantic relationship [ 39 ], and the mutual commitments (e.g., children, acquaintances, and material possessions) that partners share, partner strain among adults of all ages can potentially exacerbate negative mental health outcomes compared to the other two relationship types. 1…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, our findings extend the literature indicating the negative impact that partner strain can have on emotional states in this population. Given the effort often dedicated to maintaining partner relationships, the diminished self-worth and devalued identity following the failure of a romantic relationship [ 39 ], and the mutual commitments (e.g., children, acquaintances, and material possessions) that partners share, partner strain among adults of all ages can potentially exacerbate negative mental health outcomes compared to the other two relationship types. 1…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies with Latino populations have suggested that family support may offer coping mechanisms against life’s difficulties, buffering the risk of emotional distress [ 46 , 47 ], while family and partner strain may exacerbate life stressors [ 39 , 48 ]. Familial support may furthermore provides a safe space for individuals to discuss concerns and problems, particularly following disturbing events [ 48 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mexican‐origin individuals report higher familismo and family support than non‐Hispanic White individuals (Almeida, Molnar, Kawachi, & Subramanian, ). In general, familismo values and family support positively impact Mexican‐origin and Hispanic adults’ well‐being (Grau et al., ), particularly for low acculturated adults living in poverty (Landale, Oropesa, & Bradatan, ). Relevant to the perinatal period, higher family support has been associated with healthier maternal behaviors during pregnancy (Harley & Eskenazi, ) and better infant physical health (Sherraden & Barrera, ).…”
mentioning
confidence: 99%
“…All the adolescent mothers who were involved in the study admitted that they still have the desire to be able to gather and play with friends as before. In addition they also miss the times when they have al (14) found that the support received from a partner in a sustainable manner may reduce the pressure in being a mother at a young age. In addition support from couples to be a protective support for teenage psychic mothers.…”
Section: Resultsmentioning
confidence: 99%